Interleukin 10 attenuates neointimal proliferation and inflammation in aortic allografts by a heme oxygenase-dependent pathway - Chen, Sifeng (National Academy of Sciences, 2005)
Interleukin 10 (IL-10) is a pleiotropic cytokine with well known antiinflammatory, immunosuppressive, and immunostimulatory properties. Chronic allograft rejection, characterized by vascular neointimal proliferation, is a major cause of organ transplant loss, particularly in heart and kidney transplant recipients. In a Dark Agouti to Lewis rat model of aortic transplantation, we evaluated the effects of a single intramuscular injection of a recombinant adeno-associated viral vector (serotype 1) encoding IL-10 (rAAV1-IL-10) on neointimal proliferation and inflammation. rAAV1-IL-10 treatment resulted in a significant reduction of neointimal proliferation and graft infiltration with macrophages and T and B lymphocytes. The mechanism underlying the protective effects of IL-10 in aortic allografts involved heme oxygenase 1 (HO-1) because inhibition of HO activity reversed not only neointimal proliferation but also inflammatory cell infiltration. Our results indicate that IL-10 attenuates neointimal proliferation and inflammatory infiltration and strongly imply that HO-1 is an important intermediary through which IL-10 regulates the inflammatory responses associated with chronic vascular rejection.